2017
DOI: 10.5194/cp-13-1717-2017
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Water advection vs. glacier dynamics in northern Spitsbergen since early deglaciation

Abstract: Abstract. Atlantic Water (AW) advection plays an important role in climatic, oceanographic and environmental conditions in the eastern Arctic. Situated along the only deep connection between the Atlantic and the Arctic oceans, the Svalbard Archipelago is an ideal location to reconstruct the past AW advection history and document its linkage with local glacier dynamics, as illustrated in the present study of a 275 cm long sedimentary record from Woodfjorden (northern Spitsbergen; water depth: 171 m) spanning th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 200 publications
(275 reference statements)
4
21
0
Order By: Relevance
“…Archive halves of the sediment core were scanned by a computed tomography (CT) at the hospital Klinikum Bremen-Mitte. The CT-based IRD quantification was performed following the methodology of Bartels et al (2017). Only clast segmentation was optimized by combining threshold segmentation with a surface-volume ratio filter to remove falsely segmented bioturbation traces.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Archive halves of the sediment core were scanned by a computed tomography (CT) at the hospital Klinikum Bremen-Mitte. The CT-based IRD quantification was performed following the methodology of Bartels et al (2017). Only clast segmentation was optimized by combining threshold segmentation with a surface-volume ratio filter to remove falsely segmented bioturbation traces.…”
Section: Methodsmentioning
confidence: 99%
“…In their 10 Be-based study, Hormes et al (2011) showed that some smaller ice domes covered Nordaustlandet during the late Weichselian, probably coalescing archipelago. The entire region has been directly affected by AWadvection (Lubinski et al 2001;Slubowska et al 2005;Rasmussen et al 2007Rasmussen et al , 2012; Slubowska-Wolden-gen et al 2007;Skirbekk et al 2010;Kubischta et al 2011;Klitgaard Kristensen et al 2013; Ła z cka et al 2015; Bartels et al 2017). The present study investigates the Holocene palaeoenvironmental development within the remote Wahlenbergfjord.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In modern Greenland and Svalbard shelf and fjord environments, C. neoteretis thrives in relatively cool (À1 to 2°C), saline (34.9 practical salinity unit, psu) bottom water conditions, and C. reniforme prefers colder water (<2°C) and also relatively high salinity (>30 psu) environments (Hald & Korsun, 1997;Jennings et al, 2004;Polyak, Korsun, et al, 2002;Polyak, Levitan, et al, 2002;Steinsund et al, 1994). Thus, in Arctic shelf regions, both species are commonly associated with the advection of chilled subsurface Atlantic waters (Bartels et al, 2017;Hald & Korsun, 1997;Jennings et al, 2004;Lubinski et al, 2001;Mackensen & Hald, 1988;Polyak & Mikhailov, 1996;Polyak, Levitan, et al, 2002;Seidenkrantz et al, 2013). The relatively high abundance of N. pachyderma and the presence of heterotrophic dinocyst species in an area characterized by semiperennial sea ice cover (subdomain II) would further support the advection of Atlantic waters through subsurface currents, as planktic foraminifera likely do not live here and the specimens would all have been carried to the site from the open shelf.…”
Section: Tracing Arctic-atlantic Inflowmentioning
confidence: 99%
“…yr. BP than they are today, based on the presence of Zirfaea crispate. Bartels et al (2017) argues that sea surface temperatures were warmer at the head of Woodfjorden during the early Holocene, with reduced sea ice coverage and open waters. Alkenone-based temperature reconstructions from Amsterdamøya and Mitrahalvøya, Figure 11B, suggests an early Holocene warming of 4.5 • C at 10500 cal.…”
Section: Warm and Wet Early-and Dry Mid-holocenementioning
confidence: 99%